2005
DOI: 10.1590/s1516-35982005000500037
|View full text |Cite
|
Sign up to set email alerts
|

Biometria da carcaça e peso de vísceras e de órgãos internos de bovinos mestiços alimentados com diferentes volumosos e fontes protéicas

Abstract: RESUMO -Quarenta bovinos machos, com peso médio de 371 kg, foram distribuídos em um delineamento em blocos casualizado com esquema fatorial 3x3, dos quais quatro foram abatidos no início do experimento como referência, para avaliar a biometria das carcaças e o peso de vísceras e órgãos internos quando alimentados com diferentes fontes protéicas (uréia, Amiferm e farelo de soja) e volumosos (cana-deaçúcar e a silagem de milho e pastagem de capim Brachiaria brizantha). Não houve interação significativa volumosos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
1
8
0
6
Order By: Relevance
“…Macitelli et al (2005) also observed this same trait in a work with diets with sugar cane, corn silage and pasture, because the weights of stomach content and gastrointestinal content were greater for animals fed sugar cane, resulting in a lower empty body weight for those animals, a fact possibly explained by the inferior quality of NDF of the sugar cane and because of its greater content of NDFi in relation to the other grasses which composed the diet.…”
Section: Resultsmentioning
confidence: 71%
“…Macitelli et al (2005) also observed this same trait in a work with diets with sugar cane, corn silage and pasture, because the weights of stomach content and gastrointestinal content were greater for animals fed sugar cane, resulting in a lower empty body weight for those animals, a fact possibly explained by the inferior quality of NDF of the sugar cane and because of its greater content of NDFi in relation to the other grasses which composed the diet.…”
Section: Resultsmentioning
confidence: 71%
“…Segundo Rohr & Daenicke (1984) o conteúdo do TGI é proporcional ao tamanho das partículas do alimento e inversamente proporcional à digestibilidade da forragem. Macitelli et al (2005) também verificaram que o retículo-rúmen foi maior em animais alimentados com silagem de cana-de-açúcar em relação aos alimentados com silagem de milho e pastagem de Brachiaria brizantha. Esses autores atribuíram esse aumento ao maior tamanho de partícula da silagem de cana em relação aos demais volumosos, já que, na dieta com cana, o teor de fibra em detergente neutro (FDN) foi menor.…”
Section: Resultsunclassified
“…During the ensiling of sugarcane, an excessive loss of dry matter occurs, which is reflected in terms of animal performance. However, the evaluation of empty body weight (Macitelli et al, 2005) indicated that the beef cattle fed on sugarcane had higher weights of stomach and gastrointestinal contents, resulting in a lower empty body weight for these animals, a fact possibly could be explained by the inferior quality of NDF of the sugarcane and its greater content of NDFi in relation to the other grasses that composed the diet. However, no improvement in the performance of the animals was observed (Abrahão et al, 2007) when fed on sugarcane in natura, not even with a higher concentrate in the diet.…”
Section: Resultsmentioning
confidence: 99%